Representações e práxis integralista em Pouso Alegre-MG - Marques, Ivan Teodoro (2020)
This paper has as objectiv, to realise the representations and the activities of the Ação Integralista Brasileira in the city of Pouso Alegre-MG, thought the newspaper A Razão, part of the integralism impress that has been circulating on the city between the years of 1936 and 1937. Justifing this research the ascenption of the conservadors e nacionalism in the actual conjuntura, the resgat of the integralism memory and his signs, the importance of understanding how did the integralists conquer to many adepts for all over the country, as well highlight the presence of this ideals in the south of Minas Gerais